IMPLEMENTASI SISTEM INFORMASI WISATA ALAM DANAU TANGKAS SEBAGAI STRATEGI PENGUATAN PROMOSI PARIWISATA DI DESA LABORATORIUM TERPADU TANJUNG LANJUT KECAMATAN SEKERNAN MUARO JAMBI - Indrawijaya, Sigit; Sari, Novita; Suprayogi, Dawam; Suhartini, Sugih; Utomo, Pradita Eko Prasetyo (Jurnal Pengabdian Masyarakat Pinang Masak, 2025)
Pelayangan sub-district is a sub-district in Jambi City where the average income of the population is obtained from small and medium industries (IKM). The product produced is one of the typical products of the Jambi region, including crackers, batik, food, and others. Product marketing that has been carried out so far is still fixated using conventional methods. This is due to the limited knowledge of IKM managers in the Pelayangan District area in utilizing information technology to support the marketing process for the products they produce. With the use of social media and the development of video advertisements on social media, it is possible to expand market share and the resulting product sales transactions. For this reason, in order to expand market share, a community service program for the application of science and technology is carried out. Where in this service program, the development and implementation of assistance in the use of promotional media will be carried out in the form of product videos that are advertised premium on social media in order to expand market share in product sales to small and medium industries (IKM) in Pelayangan Kota District. Assistance activities will be carried out in 3 activity sessions located in Pelayangan District, namely 1 session of delivering material, ideas and ideas about product marketing through advertising services on social media and 2 sessions of making, implementing and mentoring the use of the media. The output resulting from this community service activity is an increase in community understanding and skills about promotion using social media and IKM product videos that are promoted through advertising services on social media.